A combination of systemic mannitol and mannitol modified polyester nanoparticles for caveolae-mediated gene delivery to the brain - Betsy Reshma Gilbert; Chirag Miglani; Arundhati Karmakar; Muneesh Pal; Vysakh C. Chandran; Sarika Gupta; Asish Pal; Munia Ganguli (Molecular Therapy: Nucleic Acids)
Overcoming the blood-brain barrier (BBB) remains a significant challenge for nucleic acid delivery to the brain. We have explored a combination of mannitol-modified poly (β-amino ester) (PBAE) nanoparticles and systemic mannitol injection for crossing the BBB. We incorporated mannitol in the PBAE polymer for caveolae targeting and selected monomers that may help avoid delivery to the liver. We also induced caveolae at the BBB through systemic mannitol injection in order to create an opportunity for the caveolae-targeting nanoparticles (M30 D90) containing plasmid DNA to cross the BBB. When a clinically relevant dose was administered intravenously in this caveolae induction model, M30 D90 demonstrated significant transgene expression of a reporter plasmid in the brain, with selective uptake by neuronal cells and minimal liver accumulation. We demonstrate that caveolae modulation using systemic mannitol administration and caveolae targeting using designed nanoparticles are necessary for efficient delivery to the brain. This delivery platform offers a simple, scalable, and controlled delivery solution and holds promise for treating brain diseases with functional targets.